2015
DOI: 10.2135/cropsci2014.03.0248
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and Genetics of Tassel Branch Numbers in Maize

Abstract: The diversity and genetics of tassel branch numbers (TBN) in maize (Zea mays L.) were evaluated in a series of five studies. Diversity was assessed in races and inbreds and genetics assessed in diallels, generation mean analyses (GMAs), near‐isogenic lines (NILs), and recombinant inbred lines (RILs). High diversity characterized 215 tropical maize races that averaged 27.0 ± 3.27 TBN and 80 modern inbreds that averaged 14.8 ± 1.45 TBN. There was a close correlation between TBN values and husk numbers (r = 0.674… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
18
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 32 publications
5
18
1
Order By: Relevance
“…We also tested the effects of Oy1-N1989 and vey1 interaction on tassel phenotypes and other axillary meristem structures such as tiller numbers in isogenic materials. A previous study identified effects of a recessive partial loss-of-function allele at oy1 on tassel branch number (Brewbaker 2015). Our results agree with Brewbaker (2015) as Oy1-N1989 decreased tassel branch number dramatically in the presence of vey1 Mo17 allele and the effect was suppressed by vey1 B73 .…”
Section: Introductionsupporting
confidence: 90%
See 1 more Smart Citation
“…We also tested the effects of Oy1-N1989 and vey1 interaction on tassel phenotypes and other axillary meristem structures such as tiller numbers in isogenic materials. A previous study identified effects of a recessive partial loss-of-function allele at oy1 on tassel branch number (Brewbaker 2015). Our results agree with Brewbaker (2015) as Oy1-N1989 decreased tassel branch number dramatically in the presence of vey1 Mo17 allele and the effect was suppressed by vey1 B73 .…”
Section: Introductionsupporting
confidence: 90%
“…A previous study identified effects of a recessive partial loss-of-function allele at oy1 on tassel branch number (Brewbaker 2015). Our results agree with Brewbaker (2015) as Oy1-N1989 decreased tassel branch number dramatically in the presence of vey1 Mo17 allele and the effect was suppressed by vey1 B73 . Remarkably in hightillering sweet corn, Tillering1 (Tlr1), teosinte branched1 (tb1) and grassy tillers1 (gt1) mutants, Oy1-N1989 reduced the number of tillers at maturity and an epistatic effect of Oy1-N1989 on tb1…”
Section: Introductionsupporting
confidence: 90%
“…We focused on traits that are related to altitude adaptation in both maize and teosinte (Lauter et al . ; Brewbaker ; Takuno et al . ) as well as on fitness‐related traits.…”
Section: Discussionmentioning
confidence: 99%
“…In order to provide an adaptive interpretation of our candidate regions, we compiled over 90 studies including association and QTL mapping studies in teosintes and/or maize, as well as functional validation studies. We focused on traits that are related to altitude adaptation in both maize and teosinte Brewbaker 2015;Takuno et al 2015) as well as on fitness-related traits. We found a total of 33 candidate regions among 47 falling within previously characterized QTL regions (Table 3).…”
Section: Gene In Common Withmentioning
confidence: 99%
“…Maize landraces (open-pollinated traditional varieties) from both populations share a number of phenotypes not found in lowland populations, including dense macrohairs and stem pigmentation (Wellhausen et al 1957;Wilkes 1977), differences in tassel branch and ear husk number (Brewbaker 2015), and a changed biochemical response to UV radiation (Casati and Walbot 2005). In spite of these shared phenotypes, genetic analyses of maize landraces from across the Americas indicate that the two highland populations are independently derived from their respective lowland populations (Vigouroux et al 2008;van Heerwaarden et al 2011), suggesting that observed patterns of phenotypic similarity are not simply due to recent shared ancestry.…”
mentioning
confidence: 99%